Severe Congenital Thrombocytopenia Characterized by Decreased Platelet Sialylation and Moderate Complement Activation Caused by Novel Compound Heterozygous Variants in GNE - Smolag, Karolina I.; Fager Ferrari, Marcus; Zetterberg, Eva; Leinoe, Eva; Ek, Torben; Blom, Anna M.; Rossing, Maria; Martin, Myriam (Frontiers in Immunology, 2021)
Background: Hereditary thrombocytopenias constitute a genetically heterogeneous cause of increased bleeding. We report a case of a 17-year-old boy suffering from severe macrothrombocytopenia throughout his life. Whole genome sequencing revealed the presence of two compound heterozygous variants in GNE encoding the enzyme UDP-N-acetyl-glucosamine-2-epimerase/N-acetylmannosamine kinase, crucial for sialic acid biosynthesis. Sialic acid is required for normal platelet life span, and biallelic variants in GNE have previously been associated with isolated macrothrombocytopenia. Furthermore, sialic acid constitutes a key ligand for complement factor H (FH), an important inhibitor of the complement system, protecting host cells from indiscriminate attack. Methods: Sialic acid expression and FH binding to platelets and leukocytes was evaluated by flow cytometry. The binding of FH to erythrocytes was assessed indirectly by measuring the rate of complement mediated hemolysis. Complement activation was determined by measuring levels of C3bBbP (alternative pathway), C4d (classical/lectin pathway) and soluble terminal complement complex assays. Results: The proband exhibited markedly decreased expression of sialic acid on platelets and leukocytes. Consequently, the binding of FH was strongly reduced and moderate activation of the alternative and classical/lectin complement pathways was observed, together with an increased rate of erythrocyte lysis. Conclusion: We report two previously undescribed variants in GNE causing severe congenital macrothrombocytopenia in a compound heterozygous state, as a consequence of decreased platelet sialylation. The decreased sialylation of platelets, leukocytes and erythrocytes affects the binding of FH, leading to moderate complement activation and increased hemolysis.